LIMA1-alpha staining predicts curative intent surgery response in HPV negative head and neck cancer - Qiao, Xi; Routila, Johannes; Tienhaara, Mari; Irjala, Heikki; Santhi, Priyadharshini Parimelazhagan; Huusko, Teemu; Nissi, Linda; Paatero, Ilkka; Lehtinen, Noora; Rantala, Juha; Viljanen, Toni; Leivo, Ilmo; et al. (Springer Science and Business Media LLC, 2026)
In many solid cancer types, surgery alone could be a sufficient first therapy option for a significant number of cancer patients. However, there are currently no diagnostic solutions to identify patients who could be stratified to surgery alone. To identify a biomarker predicting cancer surgery response, candidate biomarkers were studied in a non-metastatic head and neck squamous cell carcinoma (nmHNSCC) cohort well representative of the HPV-negative patient population. LIMA1 immunohistochemistry (IHC) with specificity-validated antibodies outperformed all other biomarkers in multivariable survival analyses of patients with nmHNSCC (n = 128, HR 2.10, P = 0.006). The prognostic effect was selective to LIMA1-alpha isoform IHC detection in patients who had received surgical therapy (n = 184, HR 2.39, P > 0.001). Strikingly, our real-world validation results, using two prospectively collected cohorts (n = 15 and n = 86), demonstrate that none of the LIMA1 negative patients died of HNSCC during the follow-up. Collectively, we report here the discovery of a diagnostic LIMA1-alpha IHC assay for HPV-negative HNSCC patient stratification to surgery-only therapy. Application of LIMA1 detection in routine nmHNSCC diagnostics would revolutionize the clinical management of HNSCC patients.